HYDROLYSATE CHARACTERISTICS OF BERUNOK SEA CUCUMBER (Paracaudina australis) AND TOTAL AMINO ACID USING PEPSIN ENZYMES - Kembaren, Bella Billiant J Ananta; Karnila, Rahman; Hasan, Bustari (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2024)
Berunok sea cucumber has a nutritional content that can be utilized as a functional food ingredient. This study determined the characteristics of berunok sea cucumber hydrolysate (Paracaudina australis) and the type and level of total amino acids. This research was conducted using experimental methods, with a Non-Factor Complete Randomized Design consisting of 3 levels of enzyme concentration treatment (1%, 2%, and 3%) with three replicates. In this study, the parameters tested were the proximate content of flour and hydrolysate of berunok and the type and content of total amino acids. The results showed that the chemical composition of berunok flour was water 11,40% (dw), ash 10,82% (dw), protein 68,21% (dw), fat 6,53% (dw), and carbohydrate by the difference of 14,43% (dw). The best treatment for preparing berunok protein hydrolysate using pepsin enzyme is 2% pepsin enzyme concentration. The proximate of berunok protein hydrolysate is water 6.87% (dw), ash 8.45% (dw), protein 80,59% (dw), and fat 2,86% (dw). The results of the identification of types and levels of total amino acids found 17 kinds of amino acids with a total of 16.524% in hydrolysate berunok.